MAPPING MARINE DEBRIS IN COASTAL AREA PADANG CITY - Pradana, Hangga; Mubarak, Mubarak; Galib, Musrifin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
This study aims to determine the distribution of types and masses of marine debris that has been carried out in July 2020 in the Coastal Coast of Padang City. The method used was a survey method. Sampling was carried out at 4 observation stations, namely Cinta Beach, Pasir Selahan Beach, and Air Manis Beach. The results showed that the types of marine debris found at the research site consisted of plastic, metal, glass, rubber, wood, cloth, and other types. The total amount of marine debris found was 1,316 pieces with a total weight of 22,047 kg. The most common type of marine debris found in plastic waste.